A Picture book of Louise Braille - Adler, David A. (U.S.A : Holiday House, 1997)
Presents the life of the nineteenth-century Frenchman , accidentally blinded as a childm who originated the raised dot system of reading and writing used throughout the world by the blind.
Keywords: Braille, Louis, 1809-1852-Juvenile literature; Braille, Louis, 1809-1852-Pictorial works-Juvenile literature; Blind teachers-France-Biography-Juvenile literature